(untitled) (Research, Society and Development, 2020)
Nicotine is a substance found in tobacco and its derivatives, with few reports in the literature related to intoxication in dogs. Toxicosis in the species can occur due to the proximity to humans, especially with smoking tutors, making contact with this substance inevitable. The present work aims to make a bibliographic review on nicotine poisoning in dogs. For the study, a search for articles indexed in the scientific bases PubMed, SciELO, portal of CAPES and Scopus journals was carried out, in the time frame from 1998 to 2020, using the following descriptors: dogs, nicotine, tobacco and intoxication. From the studies listed, the following results were obtained: which products derived from nicotine were more described in the literature, their lethal dose and the clinical signs related to toxicosis. It was concluded that nicotine is a very dangerous substance for dogs and that despite its severity, there are few studies on clinical and emergency approaches in cases of nicotine poisoning.